(untitled) (Research, Society and Development, 2020)
The article addresses questions in the field of Adapted Sports, discusses a study about the perception and methodologies of Physical Education teachers in Schools in Tocantinópolis-TO. The general objective is: To know the perception of Physical Education teachers about the application of adapted sports, for students with or without disabilities, at school. It has as question: What is the perception and methodologies of Physical Education teachers in schools in Tocantinópolis-TO in relation to Adapted Sports? In a critical line of investigation, the methodology is a study with a qualitative approach, with descriptive objectives and of an applied nature, carried out with Physical Education Teachers from the state school system, using the semi-structured interview applied as a data collection instrument. Through a questionnaire containing five open questions. It is noteworthy that the study made it possible to understand the perception of Physical Education teachers about the applicability of adapted sports, for students with or disabilities in the school context of the city of Tocantinópolis, as well as the methodological strategies used by teachers to promote the participation of these students.